Enriching employee engagement using complexity theory. (May 2021) - Lemon, Laura L.; Macklin, Chalise
This paper conceptually draws the connections between complexity theory and employee engagement. Instead of the tendency to adhere to a binary, dichotomous approach, complexity theory helps move employee engagement forward as a process that is rooted in multiplicity, intricacy, and variance. This approach provides a more sustainable future for employee engagement scholarship by reimagining the ways in which scholars investigate the phenomenon. In providing future research suggestions rooted in complexity, scholarship and practice can transition away from prescriptive, normalized processes and solutions for employee engagement to welcome various approaches that lead to more fluid and organic understanding. The goal is to set a standard of encouraging employee engagement scholars to challenge how they explore employee engagement and to welcome new and innovative ways of examining the phenomenon to provide a sustainable and enriching scholarly conversation.